المحاولات البرتغالية التوسعية في السواحل اليمنية خلال القرن العاشر الهجري/السادس عشر الميلادي وتداعياتها - فسيل، سامية محمد عبد الله
Portugal was known as a commercial and military power in the international scene since tenth century AH /sixteenth century CE. The Portuguese brought the first signs of Western colonialism in modern history to several regions of the world, including the Islamic world, which was affected by the expansion of the Portuguese to a large extent. The reason for Portugal's early prominence lies in its strategic location, richness of resources, and its power in controlling the most important shipping routes of world trade during the tenth century AH / sixteenth century CE. The coast of Yemen was one of the most important sea routes which the Portuguese attempted to control. This thesis looks at the efforts of the Portuguese to occupy the coast of Yemen in this period, and the resulting effects of these attempts on the political, economical, and commercial aspects of Yemen, and the regions of the Red Sea and the Arabian Sea. The study examines the factors for the Portuguese attack on Yemen at that time, and the role of Islamic forces in the country in confronting this attack. Moreover, the study explores the reasons behind the failure of the Portuguese to find a foothold in the islands of the coast of Yemen, despite repeated attacks by a huge military force and naval armada. The research adopted the descriptive analytical in the discussion of these issues, and consulted a multitude of primary sources and secondary references relevant to the subject of the study. Finally, the thesis found out that several factors had led to the inability of the Portuguese to colonize the land of Yemen, namely, the geographical immunity of the region, and the strong Yemeni resistance, by which the Yemenis repulsed the attacks of Portuguese by simple weapons but with the spirit of braveness and love of their country. In addition, the Islamic force that defended the region of the Red Sea, the Ottoman Empire, had protected the Red Sea from Portuguese expansionism and maintained it as a strategic region for the Islamic world.